Direct sampling of atmospheric aerosol particles during Arctic Airborne Measurement Program (AAMP 98) - Keiichiro Hara; Yasunobu Iwasaka; Yayoi Inomata; Kazuo Osada; Katsuji Matsunaga; Sadamu Yamagata; Masahiro Nagatani; Hiroshi Nakata (National Institute of Polar Research, 2002)
In order to know the morphology and mixing state of atmospheric aerosol particles in the spring Arctic atmosphere, direct sampling of aerosol particles was carried out using an aerosol impactor system during the Arctic Airborne Measurement Program (AAMP 98). Aerosol samples were observed with a scanning electron microscope and analyzed with an energy-dispersive X-ray spectrometer. Aerosol particles with clear satellite structure due to sulfuric acid droplets were observed in samples collected in the lower stratosphere and free troposphere. On the other hands, aerosol particles with crystal and satellite structure due to droplets of sea salt particles were observed in the boundary layer.